SAT0122 Efficacy of addition, or continuation, of adalimumab in patients who did not achieve stable low disease activity with methotrexate or adalimumab plus methotrexate in the optima study. (23rd January 2014) - Kavanaugh, A.; Fleischmann, R.; Emery, P.; van Vollenhoven, R.; Florentinus, S.; Shaw, J.W.; Santra, S.; Kupper, H.; Redden, L.; Smolen, J.
Abstract : Background: Guidelines for rheumatoid arthritis (RA) recommend adjusting treatment every 3-6 months to the desired state of disease activity. Patients (pts) treated with adalimumab (ADA) plus methotrexate (MTX) may have delayed responses without major radiographic consequences 1 . Objectives: To determine outcomes after introduction of ADA in pts who did not achieve a stable low disease activity (LDA) target with MTX alone compared with pts continuing ADA+MTX who did not achieve the target. Methods: MTX-naïve pts ≥18 yrs with RA <1 yr, active disease [DAS28(CRP)>3.2, ESR≥28 mm/hr or CRP≥1.5 mg/dL], and >1 erosion, RF+, or anti-CCP+ were randomized to ADA+MTX or placebo (PBO)+MTX for 26 wks. Pts who did not achieve a stable LDA target (DAS28<3.2 at wks 22 & 26) were offered open-label ADA+MTX for 52 wks. Categorical responses were analyzed using non-responder imputation and radiographic outcomes by multiple imputation. Predictors of rapid radiographic progression (RRP, ΔmTSS>1.5 in 26 wks) were assessed. Results: Among pts who completed 26 wks, 76% (348/460) PBO+MTX and 56% (259/466) ADA+MTX did not achieve the stable LDA target (inadequate response [IR]). Introduction of ADA enhanced responses among PBO+MTX[IR] pts. Improvements were also observed among ADA+MTX[IR] pts who continued ADA+MTX despite no adjustment of concomitant medications (Table ). Significantly more damage occurred in PBO+MTX[IR] pts: mean ΔmTSS from wk 0-26 was 1.2 compared with 0.3 for ADA+MTX[IR] ( P <.001). RRP occurred in 18% PBO+MTX[IR] pts, compared with 5% ADA+MTX[IR] pts. Baseline erosions were a strong predictor of RRP. Addition of ADA halted radiographic progression in PBO+MTX[IR] pts: mean ΔmTSS from wk 0-78 was 1.3; radiographic inhibition was sustained in ADA+MTX[IR] pts: mean ΔmTSS from wk 0-78 was 0.4. Conclusions: Introduction of ADA to pts who failed to achieve a stable LDA target with MTX alone decreased disease activity and halted radiographic progression; however, pts with baseline erosions may be candidates for earlier treatment intensification. Continued ADA+MTX treatment yielded ongoing improvements with little radiographic progression, demonstrating the disconnect between control of disease activity and inhibition of damage with ADA. References: Keystone et al. ACR 2011 P1102 Disclosure of Interest: A. Kavanaugh Grant/Research support from: Abbott, Amgen, Astra-Zeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB, Consultant for: Abbott, Amgen, Astra-Zeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB, R. Fleischmann Consultant for: Abbott, P. Emery Consultant for: Pfizer Inc, Merck, Abbott, Roche, BMS, UCB, R. van Vollenhoven Grant/Research support from: Abbott, Glaxo Smithkline, Merck, Pfizer, Roche, UCB Pharma, Consultant for: Abbott, Glaxo Smithkline, Merck, Pfizer, Roche, UCB Pharma, S. Florentinus Shareholder of: Abbott, Employee of: Abbott, J. Shaw Shareholder of: Abbott, Employee of: Abbott, S. Santra Shareholder of: Abbott, Employee of: Abbott, H. Kupper Shareholder of: Abbott, Employee of: Abbott, L. Redden Shareholder of: Abbott, Employee of: Abbott, J. Smolen Grant/Research support from: Abbott, Amgen, Astra-Zeneca, BMS, Celgene Centocor-Janssen, Glaxo, Lilly, Pfizer (Wyeth), MSD (Schering-Plough), Novo-Nordisk, Roche, Sandoz, UCB, Consultant for: Abbott, Amgen, Astra-Zeneca, BMS, Celgene Centocor-Janssen, Glaxo, Lilly, Pfizer (Wyeth), MSD (Schering-Plough), Novo-Nordisk, Roche, Sandoz, UCB